A proposito della diversità: essere alunni sud-asiatici nella società italiana - Zoran Lapov (Firenze University Press, 2017)
Placed at the intersection between pedagogy, anthropology and migration studies, the paper is a part of a broader research work on diversity in school and society: delving into the transcontinental experience of South Asian communities, it sheds light on some aspects characterising the sociocultural baggage of the South Asian pupils attending Italian school. In the assortment of situations that can be met in a present-day multicultural classroom, it was chosen to focus a particular attention on linguistic plurality being it one of main dimensions describing the sociocultural diversity of South Asian pupils both in their sending and receiving contexts. Thereby, the paper is interested in promoting the debate on diversity in school and society in an intercultural perspective, as well as in contributing to the research on South Asian communities in Italy.